2008
DOI: 10.1007/s00249-007-0253-0
|View full text |Cite
|
Sign up to set email alerts
|

Oriented epitaxial growth of amyloid fibrils of the N27C mutant β25–35 peptide

Abstract: Amyloid fibrils are present in the extracellular space of various tissues in neurodegenerative and protein misfolding diseases. Amyloid fibrils may be used in nanotechnology applications, because of their self-assembly properties and stability, if their growth and orientation can be controlled. Recently, we have shown that amyloid beta 25-35 (A beta 25-35) forms a highly oriented, K(+)-dependent network on mica. Here, we analyzed the properties of A beta 25-35_N27C, the cysteine residue of which may be used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…At this time it is however difficult to elucidate a precise mechanism. It could be due to the fact that, when the angle is smaller than the preferred angle, two fibers have a tendency to laterally associate or to a preferential orientation of fibrils due to interaction with mica as previously described with amyloid proteins such as α-synuclein [46] or Aß peptide [47]. This point remains to be clarified.…”
Section: Discussionmentioning
confidence: 87%
“…At this time it is however difficult to elucidate a precise mechanism. It could be due to the fact that, when the angle is smaller than the preferred angle, two fibers have a tendency to laterally associate or to a preferential orientation of fibrils due to interaction with mica as previously described with amyloid proteins such as α-synuclein [46] or Aß peptide [47]. This point remains to be clarified.…”
Section: Discussionmentioning
confidence: 87%
“…AFM imaging was carried out by using procedures reported in previous papers on Aß fibrils Kellermayer et al, 2005;Karsai et al, 2006;Karsai et al, 2007;Karsai et al, 2008;Kellermayer et al, 2008) with modifications. Hundred microliters of the diluted WT TTR sample was deposited on freshly cleaved mica, incubated for 5 min at room temperature; the surface was then rinsed with buffer.…”
Section: Atomic Force Microscopymentioning
confidence: 99%
“…An interesting thing is that because of the hexagonal structure of the HOPG lattice, particular orientations of the peptide principal axes and the assembled peptide fiber axes are observed in experiment 28. This phenomenon has also been observed for peptide adsorption on other surfaces 27, 36. We examined the peptide structures from the trajectory files, although it is regretful that we did not observe the specific orientation of the whole peptide chain with respect to the HOPG lattice due to the small timescale that all‐atom simulations could reach, we found that after depositing on the surface, most of the adjacent residues had a tendency to cover the surface in a manner parallel to the three horizontal crystallographic axes of the HOPG surface, also see our previous work for details 29.…”
Section: Discussionmentioning
confidence: 55%